2021
DOI: 10.1002/pne2.12062
|View full text |Cite
|
Sign up to set email alerts
|

BrightHearts: A pilot study of biofeedback assisted relaxation training for the management of chronic pain in children with cerebral palsy

Abstract: Background: Chronic pain is estimated to impact one-in-three children with cerebral palsy (CP). Psychological interventions including behavioral and cognitive strategies play a key role in chronic pain management, but there is a paucity of research exploring their use in children with CP.Aim: To investigate the acceptability and feasibility of biofeedback assisted relaxation training (BART) for chronic pain management in children with CP using a mixedmethods study design.Methods: Biofeedback assisted relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(50 citation statements)
references
References 38 publications
0
50
0
Order By: Relevance
“…Ostojic and colleagues report a mixed methods study assessing the acceptability and feasibility of using a biofeedback-assisted relaxation training as an intervention for chronic pain management in children with CP. 24 This pilot study highlights the ways in which biofeedback-used via an iOS application-was feasible and beneficial as noted by both children and their parents.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Ostojic and colleagues report a mixed methods study assessing the acceptability and feasibility of using a biofeedback-assisted relaxation training as an intervention for chronic pain management in children with CP. 24 This pilot study highlights the ways in which biofeedback-used via an iOS application-was feasible and beneficial as noted by both children and their parents.…”
mentioning
confidence: 86%
“…There has been a paucity of research studies broadly exploring pain treatment approaches in IDD, and even less is known about the utility of non‐pharmacological interventions. Ostojic and colleagues report a mixed methods study assessing the acceptability and feasibility of using a biofeedback‐assisted relaxation training as an intervention for chronic pain management in children with CP 24 . This pilot study highlights the ways in which biofeedback—used via an iOS application—was feasible and beneficial as noted by both children and their parents.…”
mentioning
confidence: 99%
“…33,40 However, although all studies included individuals with a diagnosis of CP, not all reported the GMFCS level of participants (n = 4). 34,35,37,41 Most studies included a description of the cognitive abilities of participants (n = 8), 29,30,33,34,[36][37][38]41 with cognitive abilities ranging from mild intellectual impairment (n = 2), 33,41 to low-average (n = 2) 29,30 and average (n = 3) 36-38 levels of intellectual abilities. Others indicated that participants had an additional medical diagnosis (e.g.…”
Section: Populationsmentioning
confidence: 99%
“…The populations of the included studies were from five different countries (Australia = four; [28][29][30]33 USA = three; [34][35][36] Canada = two; 37,38 Sweden = two; 31,32 Norway = two 39,40 ), with one study not specifying the study location. 41 A total of 107 individuals (46% females) with CP were included in the selected studies (participants in studies reporting the same population were only counted once).…”
Section: Populationsmentioning
confidence: 99%
See 1 more Smart Citation